Efikasi Diri Kader Kesehatan dalam Pengelolaan Kusta di Kabupaten Cilacap - Nadhia Elsa Silviani (Journal of Nursing and Health, 2025)
The discovery of new cases of leprosy in Cilacap Regency has increased since 2017, but the role of cadres in leprosy management in several areas has not been optimal. There needs to be an evaluation of self-efficacy in cadres in leprosy management. The purpose of this study was to see the picture of self-efficacy of health cadres in leprosy management in Cilacap Regency. The method used was a quantitative method with a descriptive research design. The sample consisted of 69 respondents taken using the randomized cluster sampling technique. The GSES questionnaire was used to measure the self-efficacy of respondents. Data analysis used frequency distribution. The results showed that the majority of health cadres were women (89.9%), housewives (57.9%), had a high school education (46.3%), had no experience receiving leprosy counseling (55.1), had experience as a cadre for 2-5 years (42%), income range 500,000-2,500,000 (43.5%), never had experience treating leprosy patients (88.4%). The majority of respondents showed poor self-efficacy in the magnitude and generality domains (42%), while a small portion showed very good categories in all three domains: magnitude (22%), strength (29%), generality (25%). The conclusion of this study is that the self-efficacy category in each self-efficacy domain varies, but the less category is more in the magnitude and generality domains. This study is expected to be input for the Health Center to improve the self-efficacy of cadres in their work areas so that the role of cadres is more optimal. In addition, further research needs to be conducted to determine the factors that influence self-efficacy in health cadres in leprosy management.